Variation in propagule and colonization pressures following rapid human‐mediated transport: Implications for a universal assemblage‐based management model. (12th October 2014) - Briski, Elizabeta; Drake, D. Andrew R.; Chan, Farrah T.; Bailey, Sarah A.; MacIsaac, Hugh J.
Abstract : Recent studies have recognized the importance of propagule pressure (number of individuals) and colonization pressure (number of species) for explaining establishment success of nonindigenous species. However, the International Ballast Water Management Convention, when ratified, will require ships to satisfy a numeric discharge standard that focuses only on cumulative propagule pressure of all individuals released. Because of practical constraints, the standard does not differentiate between discharges of single vs. multiple species. The assemblage‐based approach, which uses rank‐abundance gradients to quantify and manage introduction risk, may compensate for this limitation (e.g., even gradient [relatively consistent propagule pressures among n transported species] or uneven gradient [uneven propagule pressures among n transported species]). Here we explore species abundance distributions of zooplankton during transportation in ballast water to assess variability in the structure of assemblages, with implications for the potential development of an assemblage‐based management model. Specifically, we explored species abundance distributions for voyages that lasted < 24 h, those from 24 to 48 h, and those from 48 to 72 h (i.e., three time scales). Species abundance distributions within and across transit time scales were highly variable. As transport time increased, we observed a shift from uneven to even rank‐abundance gradients. Owing to variation in assemblage structure, the number of organisms necessary to quantify colonization pressure exhibited similarly strong variation within and across time scales. Our study indicates that assemblage‐based approaches to estimate introduction risk are warranted, yet the variation inherent in transported assemblages will induce substantial uncertainty within management models.